The application of corporate governance to the earnings management of the banking industry in Indonesia in the 2005-2007 period - Abhimayu Hendra (IHSA Institute, 2022)
The aims of this research is to examine the influence of corporate governance mechanisms, such as, board of commissioner composition and size, audit committee size, composition of independent audit committee members and their expertise on earnings management practice in public bank companies listed in Indonesia Stock Exchange. The samples of this research are all of the public bank companies that existed in Indonesia in the year 2005-2007 which were listed on the Indonesia Stock Exchange. The research data were collected from the public bank's financial statement and annual report for the period of 2005 to 2007. From purposive sampling method, I have collected 72 observations from 24 public bank companies/3 years. By using multiple regression analysis as the research method, the results showed that five independent variables influenced the earnings management of public bank companies simultaneously. The conclusion of this research is only board commissioner composition and audit committee expertise that significantly affects earnings management, while board commissioner size, composition of independent audit committee members and size has no significant effect on earnings management.